Strategi Komunikasi Bengkel Choyan Garage Auto Service Car Cilegon Untuk Memelihara Kesetiaan Konsumen - Jannah, Fahisatul; Nashrudin, Achmad; Fajarwati, Noerma Kurnia; Laksana, April; Handayani, Putri (Innovative: Journal Of Social Science Research, 2025)
This study examines the communication strategy of Choyan Garage Auto Service Car Cilegon in maintaining customer loyalty amid the increasingly competitive automotive service sector. The research applies a descriptive qualitative approach with data collected through interviews, observations, and documentation. Theoretical frameworks used include the Elaboration Likelihood Model (ELM), which explains message processing through central and peripheral routes, and Uses and Gratifications, which explores consumers’ reasons for choosing particular communication media. The findings reveal that the central route is implemented through detailed and transparent technical explanations, fulfilling customers’ cognitive needs. Meanwhile, the peripheral route is reflected in the use of social media, particularly TikTok, to present promotions, testimonials, and engaging visual content that appeals to emotional and entertainment needs. The combination of these two approaches has proven effective in building trust and sustaining customer loyalty.